Spectroscopic study of binding of a cationic Pheophorbide-a to an antiparallel quadruplex Tel22 - Ryazanova, O.A.; Zozulya, V.N.; Voloshin, I.M.; Glamazda, A.Yu.; Dubey, I.Ya.; Dubey, L.V.; Karachevtsev, V.A. (Вiopolymers and Cell, 2019)
Aim. To study the binding of a water-soluble cationic Pheophorbide-a derivative (CatPheo-a) ta a Na+–stabilized antiparallel quadruplex formed by 22-mer oligonucleotide d[AG3(T2AG3)3] of the human DNA telomeric sequence (Tel22, PDB ID: 143D). Methods. Absorption and polarized fluorescence spectroscopy were used to determine the properties of DNA–ligand complexes. Fluorescence titration was applied to evaluate the Tel22 dye binding affinity. Absorption melting was used to estimate the effect of CatPheo-a on thermodynamic parameters of the Tel22 quadruplex folding. IR spectroscopy was used to detect singlet oxygen generation . Results. CatPheo-a was found to bind effectively to the Tel22 quadruplex via two competitive binding modes, which are characterized by opposite changes in the dye fluorescence. The spectroscopic properties of CatPheo-a + Tel22 complexes were determined. Thermodynamic parameters of the Tel22 quadruplex folding with/without CatPheo-a were calculated. Conclusions. CatPheo-a destabilizes the quadruplex structure of Tel22 with a two-fold decrease in the equilibrium quadruplex folding constant at 37°C. The efficiency of singlet oxygen generation by CatPheo-a is higher than that by the anionic Pheo-a.